2020
DOI: 10.1021/acs.chemmater.0c01553
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Stabilization of TiO2–Nb2O5 Wadsley–Roth Shear Phases and Their Prospects for Lithium-Ion Battery Anode Materials

Abstract: Wadsley−Roth phases accommodate variable cation charge by crystallographic shear planes delineating blocks of the parent ReO 3 structure. The homologous series TiNb x O 2+2.5x provides possible new anode materials for lithium-ion batteries. The thermodynamic stability of three of these shear phases was determined by high-temperature oxide melt solution calorimetry. TiNb 2 O 7 , TiNb 24 O 62 , and TiNb 5 O 14.5 (often called Ti 2 Nb 10 O 29 ) all have positive enthalpies of formation from binary oxides (TiO 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
(79 reference statements)
0
50
0
Order By: Relevance
“…It should be noticed that the recent study about the entropy stabilization of TiO 2 -Nb 2 O 5 Wadsley-Roth shear phases indicated that TiNb 24 O 62 may convert into energetically more stable phases during repeated cycling in batteries, which will affect the long-term cycling stability. [51] Tetragonal PNb 9 O 25 with the space group of I4/m belongs to Wadsley-Roth phases with (3 × 3) ∞ ReO 3 structure blocks. As shown in Figure 9c, the crystalline structure of PNb 9 O 25 is built up from nine NbO 6 octahedra corner-share to form a 3 × 3 block in the ab plane, and these blocks are held together by cornersharing PO 4 tetrahedra.…”
Section: Tinb 24 O 62 Pnb 9 O 25 and Vnb 9 O 25mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that the recent study about the entropy stabilization of TiO 2 -Nb 2 O 5 Wadsley-Roth shear phases indicated that TiNb 24 O 62 may convert into energetically more stable phases during repeated cycling in batteries, which will affect the long-term cycling stability. [51] Tetragonal PNb 9 O 25 with the space group of I4/m belongs to Wadsley-Roth phases with (3 × 3) ∞ ReO 3 structure blocks. As shown in Figure 9c, the crystalline structure of PNb 9 O 25 is built up from nine NbO 6 octahedra corner-share to form a 3 × 3 block in the ab plane, and these blocks are held together by cornersharing PO 4 tetrahedra.…”
Section: Tinb 24 O 62 Pnb 9 O 25 and Vnb 9 O 25mentioning
confidence: 99%
“…It should be noticed that the recent study about the entropy stabilization of TiO 2 ‐Nb 2 O 5 Wadsley–Roth shear phases indicated that TiNb 24 O 62 may convert into energetically more stable phases during repeated cycling in batteries, which will affect the long‐term cycling stability. [ 51 ]…”
Section: Electrochemical Reaction Mechanismsmentioning
confidence: 99%
“…This suggests that the ordering of defects is thermodynamically favorable. Recently, Voskanyan and Navrotsky showed that TiO 2 -Nb 2 O 5 Wadsley-Roth CS phases are energetically metastable and stabilized via configurational entropy arising from the cation disorder at elevated temperatures ( Voskanyan et al, 2020 ). In many oxides, defect clustering at the short-range scale is energetically more favorable and long-range ordering of vacancies does not take place.…”
Section: Perovskite and Related Structuresmentioning
confidence: 99%
“…[12][13][14][15] The commercialized Li 4 Ti 5 O 12 is a typical representation, which possesses a high working potential of 1.55 V. However, its low capacity is still the main problem at present. Other Ti-based oxides, such as TiO 2 , [16] TiNb 2 O 7 , [17] Li 2 MgTi 2 O 5 , [18] etc., also operate at relatively high average potentials, possessing relatively low energy density as anode materials for LIBs.…”
Section: Introductionmentioning
confidence: 99%